POTASSIUM CHANNELS AS DRUGS TARGETS IN THERAPY OF CARDIOVASCULAR DESEASES: 25 YEARS LATER - Protić Dragana; Todorović Zoran; Gojković Bukarica Ljiljana (Sanamed, 2013)
Potassium channels are the most variable ion channel group. They participate in numerous cardiovascular functions, for example regulation of vascular tone, maintenance of resting cardiac membrane potential and excitability of cardiac conduction tissue. Both drugs and endogenous ligands could modulate potassium channel function, belonging to the potassium channel blockers or openers. Modulation of potassium channels could be a therapeutic or adverse drug action. Class III antiarrhythmic agents block the potassium channels, thereby prolonging repolarization phase of action potential with resulting prolongation of effective refractory period. Their effectiveness against supraventricular and ventricular arrhythmias should be weighted against their proarrhythmogenic potential. In addition, numerous other antiarrhythmic agents could modulate potassium channels as well. Diazoxide, minoxidil and nicorandil (well known arterial vasodilators), as well as numerous newly synthesized substances with still unknown therapeutic potential, belong to the potassium channel activators/ openers. Therapeutic use of such vasodilators may involve treatment of hypertension (diazoxide, minoxidil) and stable angina (nicorandil). Their use might be accompanied with side effects, such as vasodilation, edema, hypotension and reflex tachycardia. Potassium channel openers have also an important role in the treatment of peripheral vascular disease and pulmonary hypertension. In the future, drugs with selective effects on the vascular or cardiac potassium channels could be useful therapeutic agents.